Some Summation Theorems for Truncated Clausen Series and Applications (Analysis in Theory and Applications, 2023)
The main aim of this paper is to derive some new summation theoremsfor terminating and truncated Clausen's hypergeometric series with unit argument,when one numerator parameter and one denominator parameter are negative integers.Further, using our truncated summation theorems, we obtain the Mellin transforms ofthe product of exponential function and Goursat's truncated hypergeometric function.